A preliminary appraisal of Baitadi Phosphorite, far western Nepal (Journal of Nepal Geological Society, 1985)
The phosphorite-bearing Baitadi Carbonate Formation is investigated in the Lesser Himalaya of Far Western Nepal. The formation is divisible into seven different lithological members and the phosphorite horizon is confined in the Massive Cherty Dolomite Member. The results of preliminary prospecting works are presented.